Myelin‐associated glycoprotein alters the neuronal secretome and stimulates the release of TGFβ and proteins that affect neural plasticity. Issue 22 (23rd September 2022) - Stewart, Vanessa D.; Cadieux, Justine; Thulasiram, Matsya R.; Douglas, Tinsley Claire; Drewnik, Dennis A.; Selamat, Suhaila; Lao, Ying; Spicer, Victor; Hannila, Sari S.
Abstract : Myelin‐associated glycoprotein (MAG) and Nogo inhibit neurite outgrowth by binding to receptors such as NgR1, PirB and LRP1, and they have also been shown to induce phosphorylation of Smad2, a key intermediate in the transforming growth factor β (TGFβ) signalling pathway. In this study, we determined that MAG and Nogo do not transactivate the TGFβ receptor through their canonical receptors or discoidin domain receptor 1, which we identified as a novel receptor for MAG and Nogo. Instead, MAG and Nogo promoted Smad2 phosphorylation by stimulating secretion of TGFβ. Proteomic analysis of the neuronal secretome revealed that MAG also regulated the secretion of proteins that affect central nervous system plasticity—inducing the secretion of S100A6, septin‐7 and neurofascin 186, while inhibiting the secretion of frataxin, MAP6, syntenin‐1 and GAP‐43. This represents a novel function for MAG that has broad implications for the treatment for spinal cord injury. Abstract : In this study, we show that soluble forms of myelin‐associated glycoprotein (MAG) and Nogo induce secretion of transforming growth factor β in neurons. MAG also has broad effects on the neuronal secretome, promoting secretion of proteins that negatively affect neuronal survival, while inhibiting the secretion of factors that promote axonal growth and synaptogenesis.